Proceedings of the 5th European Conference on Computer Systems 2010
DOI: 10.1145/1755913.1755919
|View full text |Cite
|
Sign up to set email alerts
|

Transactional memory support for scalable and transparent parallelization of multiplayer games

Abstract: In this paper, we study parallelization of multiplayer games using software Transactional Memory (STM) support. We show that the STM provides not only ease of programming, but also better performance than that achievable with stateof-the-art lock-based programming, for this realistic high impact application.For this purpose, we use a game benchmark, SynQuake, that extracts the main data structures and the essential features of the popular game Quake. SynQuake can be driven with a synthetic workload generator t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Usually they are based on the use of software implementations of transactional memory, with varying results in terms of performance. Examples of such efforts include Delaunay triangulation [10], minimum spanning forest of sparse graphs [11] Lee routing algorithm [12], multiplayer game servers such as QuakeTM [13] and Atomic Quake [14] (based on a lock-based version of Quake [15]) and SynQuake [16]; or benchmarks (STMBench7 [17], STAMP [18] and RMS-TM [19], all of them composed of a number of applications representative of a variety of application domains.…”
Section: Survey Of Prior Work Supporting Tm Use Cases Usability and mentioning
confidence: 99%
See 1 more Smart Citation
“…Usually they are based on the use of software implementations of transactional memory, with varying results in terms of performance. Examples of such efforts include Delaunay triangulation [10], minimum spanning forest of sparse graphs [11] Lee routing algorithm [12], multiplayer game servers such as QuakeTM [13] and Atomic Quake [14] (based on a lock-based version of Quake [15]) and SynQuake [16]; or benchmarks (STMBench7 [17], STAMP [18] and RMS-TM [19], all of them composed of a number of applications representative of a variety of application domains.…”
Section: Survey Of Prior Work Supporting Tm Use Cases Usability and mentioning
confidence: 99%
“…Is Software Transactional Memory (STM) faster then locks in a real world application, and not just toy laboratory benchmarks? SynQuake [16] used a form of Quake, a game server reimplemented using pure Software TM (STM) from locks to examine the performance and scalability difference of TM without hardware support. Parallelization of multi-player game code for the purposes of scaling the game server is inherently difficult.…”
Section: Survey Of Prior Work Supporting Tm Use Cases Usability and mentioning
confidence: 99%
“…They were able to achieve better performance; however, the the overheads incurred by STM were again high. A subsequent study by Lupei et al [29,30] introduced SynQuake, an STM-based server derived from Quake III. These results were more promising, reporting better performance and scalability than lockbased strategies.…”
Section: Optimizing a Stand Alone Servermentioning
confidence: 99%
“…In most cases, one quantifiable metric such as server throughput ( [27]), or frame execution time ( [28] [29,30]) is used in an ad hoc fashion, without thorough consideration of how that metric relates to the underlying performance.…”
Section: Optimizing a Stand Alone Servermentioning
confidence: 99%
“…In the former category, studies by Rossbach et al [28] and Pankratius and Adl-Tabatabai [24] have shown that TM can simplify the creation of new software. Similarly, there are several microbenchmark and benchmark suites that demonstrate the use of TM, most notably STAMP [23], EigenBench [15], Atomic Quake [37], Lee-TM [2], SynQuake [20], and RMS-TM [16].…”
Section: Introductionmentioning
confidence: 99%